2002
DOI: 10.1002/biof.5520160102
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust particles induce an inflammatory response in airway epithelial cells: Involvement of reactive oxygen species

Abstract: Epidemiological studies have shown that high particulate air pollution is associated with an increase in hospital admissions for respiratory diseases and with an exacerbation of asthma symptoms [8]. In urban areas, traffic appears to be the main source of particulate airborne pollutants. Diesel engine powered cars, which produce the most abundant components of PM2.5 (Particulate Matter 2.5 µm), are suspected to be responsible for this exacerbation of respiratory diseases but their real impact on health has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Much attention has focused on the capacity of DEP to elicit oxidative stress in the lung as the trigger for upregulating these pathways, specifically the redox-sensitive transcription factors NF-B and activator protein-1 (AP-1). Consistent with this, addition of DEP to bronchial epithelial cell cultures has been shown to induce cytokine production associated with activation of NF-B and AP-1 and their associated upstream MAPKs (2,4,6,7,14,15,18,26,37). Furthermore, treatment of epithelial cells and macrophages with antioxidants has been shown to reduce DEP-induced cytokine production by downregulating the activation of these signaling pathways (6,14,15,18,37).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Much attention has focused on the capacity of DEP to elicit oxidative stress in the lung as the trigger for upregulating these pathways, specifically the redox-sensitive transcription factors NF-B and activator protein-1 (AP-1). Consistent with this, addition of DEP to bronchial epithelial cell cultures has been shown to induce cytokine production associated with activation of NF-B and AP-1 and their associated upstream MAPKs (2,4,6,7,14,15,18,26,37). Furthermore, treatment of epithelial cells and macrophages with antioxidants has been shown to reduce DEP-induced cytokine production by downregulating the activation of these signaling pathways (6,14,15,18,37).…”
mentioning
confidence: 53%
“…Instillation of DE particle (DEP) extracts into the nose has also been shown to increase the production of mucosal T helper type 2 (Th2)-related cytokines in atopic volunteers (10). Similarly, bronchial epithelial and macrophage cell lines, as well as primary cultures of bronchial epithelial cells, have been shown to release a variety of chemokines and cytokines when treated with DEP or their organic extracts (2,4,6,7,14,15,18,26,37). The cellular and molecular mechanisms underlying these inflammatory responses remain unresolved.…”
mentioning
confidence: 99%
“…Transgene expression of GM-CSF by AECs induces sensitization to aerosolized OVA with a concomitant increase in mature DC (41)(42)(43). We as well as others have shown that ambient PM or DEP induce GM-CSF in HBEC (22,23,25) via the induction of reactive oxygen species and activation of MAPK pathways (ERK1/2, p38) (39,44). We therefore hypothesized that GM-CSF was a likely candidate for DC maturation induced by DEP-treated HBEC.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding pathway 2, pulmonary oxidative stress may be responsible for instigating the systemic CV pro-oxidative [61][62][63][64][65][66][67][68] and pro-inflammatory [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] chain reaction observed after PM exposure. Cardiac tissue oxidative stress increases within hours of PM 2.5 inhalation [61], whereas footprints (e.g.…”
Section: Biological Mechanismsmentioning
confidence: 98%